Strategies for Optimizing the Morphology of CsSnI3 Perovskite Solar Cells - Zhang, Minhao; Chen, Kunli; Wei, Yunxiao; Hu, Wenzheng; Cai, Ziyu; Zhu, Junchi; Ye, Qiufeng; Ye, Feng; Fang, Zebo; Yang, Lifeng; Liang, Qifeng (Crystals (Basel), 2023)
Over the past decade, organic–inorganic hybrid perovskite solar cells (PVSCs) have shown unprecedented growth in power conversion efficiency (PCE) from 3.8% to 25.7%. However, intrinsic thermal instability and lead toxicity are obstacles limiting its large–scale commercialization. Thus, all-inorganic CsSnI3 perovskite has drawn remarkable interest owing to its nontoxicity, excellent thermal stability, low-cost fabrication, and spectacular photoelectric characteristics, including ideal bandgap range, long carrier lifetime, and large absorption coefficient. Many studies have shown that the device performances are closely related to the morphology and crystallinity of perovskite films. In this review, the physical properties of CsSnI3 perovskite are summarized. Furthermore, this review primarily narrates the recent progress in optimizing the morphology by various strategies such as additive engineering, composition regulation, and deposition techniques, emphasizing their effects on grain sizes, film uniformity, grain boundary, and defect passivation.